2020
DOI: 10.1007/s00267-020-01328-y
|View full text |Cite
|
Sign up to set email alerts
|

The Knowledge and Value Basis of Private Forest Management in Sweden: Actual Knowledge, Confidence, and Value Priorities

Abstract: With growing demands on forests, there is a need to understand the drivers of managing the forest for diverse objectives, such as production, recreation, and climate adaptation. The aim of this study was to examine the knowledge and value basis of forest management behaviors, including different management strategies and management inactivity, among private forest owners in Sweden. Different dimensions of knowledge (declarative and procedural knowledge, assessed in terms of objective and subjective knowledge m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 88 publications
2
8
1
Order By: Relevance
“…Environmental forest values, on the other hand, positively affected restoration, leaving forests untouched and applying more mixed and broad-leaved species. This result is in line with studies that show that values affect management behavior (e.g., Eriksson and Fries 2020). Based on our analysis, we argue that the methods and tools for management planning (e.g., forest management plan and certification schemes) and forestry operations (e.g., mechanized harvesting) are typically standardized, production-oriented, and influenced by the economy of scale adapted to the logistic and production systems of the large-scale forestry.…”
Section: Discussionsupporting
confidence: 92%
“…Environmental forest values, on the other hand, positively affected restoration, leaving forests untouched and applying more mixed and broad-leaved species. This result is in line with studies that show that values affect management behavior (e.g., Eriksson and Fries 2020). Based on our analysis, we argue that the methods and tools for management planning (e.g., forest management plan and certification schemes) and forestry operations (e.g., mechanized harvesting) are typically standardized, production-oriented, and influenced by the economy of scale adapted to the logistic and production systems of the large-scale forestry.…”
Section: Discussionsupporting
confidence: 92%
“…Gender has also been connected to the group of passive forest owners. In the review of Matilainen and Lähdesmäki (2023), being female (Eriksson and Fries 2020) or being a highly educated male (Malovrh et al 2015) were both attributes connected to passive forest owners.…”
Section: The Concept Of 'Active Forest Owner'mentioning
confidence: 99%
“…Forest owners with medium to large scale properties were wellrepresented within the CM category (data not shown). Owners with larger property sizes have in previous studies been shown to have more objective knowledge of forest management and of adaptation to climate change (Eriksson & Fries, 2020).…”
Section: Societal Challenge # 1: Climate Changementioning
confidence: 99%
“…Based on the given responses for undertaken forest management activities, our study revealed a more active approach to forest management among CMs compared to the other categories, resulting in a more frequent establishment of broadleaved stands and mixed forest (Fig 3). Increased social interaction among owners can contribute to a greater openness and connectedness, which may motivate them to become more active forest owners (Eriksson & Fries, 2020). CMs more frequently took part in meetings arranged by the SFA (Fig 9 , Appendix A).…”
Section: Societal Challenge # 1: Climate Changementioning
confidence: 99%